Stem cell protein Piwil2 modulates chromatin modifications upon cisplatin treatment - Wang, Qi-En (2011)
Piwil2 (mili in mouse or hili in humans), a member of the PIWI/Argonaute gene family, plays important roles in stem cell self-renewal, RNA silencing, and translational regulation in various organisms. Recent demonstration of stable Piwil2 expression in pre-cancerous stem cells and in various human and animal tumor cell lines suggests its association in tumorigenesis. Here, we show that cisplatin induces chromatin relaxation in Mili-Wild type (WT) mouse embryonic fibroblasts (MEFs), but not in Mili-knockout (KO) MEFs. Moreover, in contrast to Mili-WT MEFs, Mili-KO MEFs showed a discernable H3 hypoacetylation response upon cisplatin treatment. Levels of the histone acetyltransferase (HAT), p300, were dramatically different due to a consistent cisplatin post-treatment decrease in Mili-WT and an increase in Mili-KO MEFs. Concomitant reduction of specific HAT activity of p300 could explain the decrease of H3 acetylation in Mili-KO MEFs. Our data also shows Mili is required for maintaining the euchromatic marks in MEFs upon cisplatin treatment. In addition, Mili-KO MEFs exhibited a significant deficiency in repairing cisplatin-induced DNA damage and displayed higher sensitivity to cisplatin. Further analysis revealed that Piwil2 was also enhanced in two completely different cisplatin-resistant ovarian cancer cell lines. Interestingly, knockdown of Piwil2 expression in these two cell lines also resulted in their enhanced sensitivity to cisplatin and decreased their efficiency for removing cisplatin-induced DNA intrastrand crosslinks (Pt-GG). The overall data showed that Piwil2 is a key factor in regulating chromatin modifications especially in response to cisplatin. To conclude, the overexpression of Piwil2 in some cancers could lead to cellular cisplatin resistance, possibly due to enhanced chromatin condensation affecting normal DNA repair.